2016
DOI: 10.1155/2016/5098591
|View full text |Cite
|
Sign up to set email alerts
|

Individual Differences in Behavioural Despair Predict Brain GSK-3beta Expression in Mice: The Power of a Modified Swim Test

Abstract: While deficient brain plasticity is a well-established pathophysiologic feature of depression, little is known about disorder-associated enhanced cognitive processing. Here, we studied a novel mouse paradigm that potentially models augmented learning of adverse memories during development of a depressive-like state. We used a modification of the classic two-day protocol of a mouse Porsolt test with an additional session occurring on Day 5 following the initial exposure. Unexpectedly, floating behaviour and bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
47
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(55 citation statements)
references
References 68 publications
7
47
0
1
Order By: Relevance
“…Eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) are the two major n -3 long-chain polyunsaturated fatty acids ( n -3 LCPUFA) derived from fish and shellfish; they are essential for maintaining cellular membrane function and affect neurotransmitter release and modify receptor binding [ 15 ]. We should pay attention to the potential mechanisms that originate from models for depression with limitation when it comes to the comparability with human depression/depressive symptoms [ 16 , 17 ]; however, experimental studies have shown that these fatty acids have anti-inflammatory [ 18 ], antioxidative [ 19 ], neuroprotective [ 20 ], and neurogenesis effects [ 21 ]. These factors may also be important in protecting against depression and inflammation-related diseases [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) are the two major n -3 long-chain polyunsaturated fatty acids ( n -3 LCPUFA) derived from fish and shellfish; they are essential for maintaining cellular membrane function and affect neurotransmitter release and modify receptor binding [ 15 ]. We should pay attention to the potential mechanisms that originate from models for depression with limitation when it comes to the comparability with human depression/depressive symptoms [ 16 , 17 ]; however, experimental studies have shown that these fatty acids have anti-inflammatory [ 18 ], antioxidative [ 19 ], neuroprotective [ 20 ], and neurogenesis effects [ 21 ]. These factors may also be important in protecting against depression and inflammation-related diseases [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Porsolt test (PT) is a validated test evaluating depressive-like behaviors and coping strategies [ 79 , 80 ]. In the present study, we assessed depressive-like behavior with PT since depression is frequently identified in elderly individuals, also at subthreshold levels and with a high prevalence in the community-dwelling elderly individuals [ 81 , 82 ].…”
Section: Methodsmentioning
confidence: 99%
“…Reports have suggested that GSK-3β might have a broader function in regulation of the behavioral domain. However, there have been contradictory results concerning GSK-3β expression and activity in some studies of depressive models [10][11][12][13]. Therefore, a depressive mice model was established to study the role of GSK-3β and related signalling pathways.…”
Section: Introductionmentioning
confidence: 99%